2010
DOI: 10.1007/s10705-010-9365-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increased N use and dry periods on N2O emission from a fertilized grassland

Abstract: To better understand the effects of increased N input and dry periods on soil nitrous oxide (N 2 O) emission, we examined a unique data-set of weather, soil microclimate, N input, and N 2 O emissions (using the eddy covariance method), measured at a fertilized grassland over the period 2003-2008. We found that the N 2 O emission (11.5 kg N ha -1 year -1 ), the ratio of N 2 O emission to N input (3.4), and the duration of elevated N 2 O flux (57 days) in 2003 were about two times greater than those of the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 59 publications
1
26
1
Order By: Relevance
“…Field studies have observed increased soil N 2 O flux following wetting in cropland (Barton et al, 2008), grazed pasture (Kim et al, 2010a), tropical forest (Butterbach-Bahl et al, 2004), grassland (Hao et al, 1988), savannah (Martin et al, 2003), and fen (Goldberg et al, 2010a). Laboratory incubation experiments with cropland (Beare et al, 2009), forest (Dick et al, 2001), grassland , and peatland soils (Dinsmore et al, 2009) have yielded similar results of increased N 2 O flux after rewetting.…”
Section: Nitrous Oxidementioning
confidence: 91%
“…Field studies have observed increased soil N 2 O flux following wetting in cropland (Barton et al, 2008), grazed pasture (Kim et al, 2010a), tropical forest (Butterbach-Bahl et al, 2004), grassland (Hao et al, 1988), savannah (Martin et al, 2003), and fen (Goldberg et al, 2010a). Laboratory incubation experiments with cropland (Beare et al, 2009), forest (Dick et al, 2001), grassland , and peatland soils (Dinsmore et al, 2009) have yielded similar results of increased N 2 O flux after rewetting.…”
Section: Nitrous Oxidementioning
confidence: 91%
“…Both water and N additions significantly increased the peak effluxes in different treatments (P < 0.01), and the interactive effect between water and N addition affected the peak effluxes among the different treatments (P < 0.05). The functions of N and water addition in improving soil N 2 O effluxes are described as follows: (1) N input provides sufficient substrate for the N 2 O generation processes; (2) the drying-rewetting transformation after water addition allows the release of several organic and inorganic substances into the soil, which provides sufficient substrates and energy for nitrification and denitrification (Mummey et al, 1994;Bollmann and Conrad, 1998;Beare et al, 2009); and (3) the variations in soil NO 3 À and NH 4 + contents suggest that water addition facilitates the immediate transfer of fertilizers to mineral N from surface soil to the 0-10 cm soil layer, which also provides ample substrate for nitrification and denitrification (Goldberg et al, 2010;Kim et al, 2010). Short bursts of N 2 O emissions after fertilization were also observed in previous studies (Dobbie and Smith, 2003;Jones et al, 2007); however, the highest effluxes observed in our study was in the lower range relative to the peak values of N 2 O obtained by some other N addition experiments in temperate grasslands abroad (ranged from 100 to 7500 mg m À2 h À1 N 2 O-N) (e.g., Kim et al, 2010;Pinto et al, 2004;Van Beek et al, 2011).…”
Section: Main Influence Factors On N 2 Effluxes Under Water and N Addmentioning
confidence: 99%
“…In late June 2010, when the peaks of N 2 O effluxes were observed, the WFPS was nearly the lowest during the whole growing season; the highest N 2 O effluxes under drought soil water condition (WFPS < 30%) were also observed in previous studies both in fertilized (Zhang and Han, 2008;Peng et al, 2011) and native grasslands (Du et al, 2006;Yao et al, 2010) in Inner Mongolia. The processes of N 2 O production were generally considered depressed in such droughtaffected soil conditions, whereas Kim et al (2010) and Cantarel et al (2011) found that greater N 2 O emissions occurred under drought conditions in the European temperate grasslands. The high soil temperature could contribute to the high N 2 O emission rates during the drought period, both in the current study and in the previous studies with similar results; the N 2 O effluxes during the drought period showed positive correlation with soil temperature (Peng et al, 2011;Kim et al, 2010).…”
Section: Main Influence Factors On N 2 Effluxes Under Water and N Addmentioning
confidence: 99%
See 2 more Smart Citations